Skin cancer in outdoor workers exposed to solar radiation: a largely underreported occupational disease in Italy. (1st August 2019) - Gobba, F.; Modenese, A.; John, S.M.
Abstract: Background: Solar UV radiation (sUVR) is one of the main carcinogen exposures in occupational settings, and UV‐induced skin cancers are the most frequent tumours in fair‐skinned individuals worldwide. Objectives: According to this premise, we should expect a high number of occupational skin cancers reported to the national workers' compensation authorities each year, also considering that the incidence of skin cancers has been constantly increased in recent years Methods: We examined the data on reported non‐melanoma skin cancers (NMSC) and actinic keratoses (AK) to the Italian National Workers Compensation Authority (INAIL) from 2012 to 2017, and we compared the number of reported skin cancers for outdoor workers with the expected numbers, obtained from currently available NMSC incidence rates for the Italian population applied to the occupational sUVR‐exposed workers estimated with the CAREX methodology in Italy in 2005. Results: The cases of NMSC reported each year to INAIL in Italy are 34 per year on average, while for AK the mean number of reported cases is of only 15/year. We estimated a number of expected NMSC cases in Italy for solar UV‐exposed workers ranging between 432 and 983, representing a proportion between reported vs. expected skin cancers of only 3.5–6.2%. Conclusions: Our study clearly shows that occupational skin cancers in Italy are largely underreported, and, accordingly, urgent initiatives should be taken to raise appropriate awareness to the problem of occupational sUVR‐induced skin cancers, so that adequate preventive measures can be implemented rapidly.